Microenvironment immune response induced by tumor ferroptosis—the application of nanomedicine - Yun, Tian; Liu, Zhenzhu; Wang, Jianbo; Wang, Rui; Zhu, Liang; Zhu, Zheng; Wang, Xuejian (Frontiers in Oncology, 2022)
Ferroptosis is a non-apoptotic regulatory form of cell death that has sparked significant interest and research in cancer treatment and certain small chemical inducers have been used in the clinic. These inducers’s weak water solubility, poor targeting, rapid metabolism; and other undesirable characteristics; however, for therapeutic approaches that combine immunotherapy and ferroptosis, challenges such as medication delivery, the complexity of the tumor microenvironment, and immunosuppression remain. The targeted, low toxicity, and efficient distribution benefits of nanotechnology have considerably enhanced the therapeutic efficacy of combining immunotherapy with ferroptosis. This paper describes the distinct mechanism of ferroptosis in tumor therapy and immunotherapy, as well as the application and benefits of nanotechnology in the combination of tumor immunotherapy and ferroptosis.